Nigerian English and the Dilemma of Standard English Language Learners - Gaji, Zannah Baba; Falmatami, Kyari Sheriff; Mohammed, Maryam (NIU Journal of Humanities, 2018)
This paper reports on the dilemma learners face when learning English as a second language. Specifically the paper focuses on Nigerian englsih language learners considering various varieties of English use in Nigerian. The main objective of the paper is examines the variety of language learners in institutional settings often encounter in the process of learning English as a second language. Employing qualitative approach and desk-based method of data collection, the paper found out that, there are mainly three varieties of English in Nigeria viz: typical Nigerian English, Pidgin English and Broken English. The study concludes that more attention should be given to Standard English language in the instructional settings so that students should not be left in the dark.